Normalization of Bone Conduction Auditory Brainstem Evoked Responses in Normal Hearing Individuals - Turkman, Tuba; Kaygusuz, Irfan; Basar, Figen; Karlidag, Turgut; Keles, Erol; Birkent, Omer Faruk; Yalcin, Sinasi (Aves, 2018)
OBJECTIVES: Auditory brainstem responses (ABR) are used to evaluate the peripheral and central functions of the auditory tract. Air and bone-conduction auditory stimuli are used to evaluate the type and degree of hearing loss. The wave latencies and interpeak latencies (IPLs) are the important diagnostic data in ABR tests. Gender and age of the patients are some of the factors affecting these latencies. This study investigated the effects of age and gender on the wave and IPLs of bone-conduction ABR. MATERIALS and METHODS: One hundred healthy individuals (50 women and 50 men) aged between 10 and 60 years were enrolled into this study, and both ears of all subjects (200 ears total) were included in the assessments. Based on their age, the subjects were equally divided into five groups, and each group consisted of 10 men and 10 women. RESULTS: The findings showed a significant difference in wave latencies and IPLs between the two genders (p<0.05). Depending on stimulus intensity, wave latencies also showed statistically significant differences between the age groups (p<0.05). However, no significant difference was noted between the age groups regarding IPLs. CONCLUSION: Normative values that covered wave latencies and IPLs evoked at stimulus intensities of 50, 30, and 10 dB nHL were established for the clinical use and use as a reference for the bone-conduction ABR testing procedure.
37th Turkish National Congress of Otorhinolaryngology and Head and Neck Surgery -- OCT 28-NOV 01, 2015 -- Antalya, TURKEY
Keywords: Bone-conduction auditory brainstem responses; age; gender